Waste management in Algeria : role of the National Waste Agency (AND) - Benaissa, Ziane; Abdessalam, Amira (Laghouat : Université Amar Telidji - Département de biologie, 2023)
The increasing amount of waste is a global and national environmental problem . Waste management is a major challenge in Algeria due to its negative ecological and economic impact if done wrong. Standing today, the largest and most effective organization at implementing effective means of waste management is the AND (National Waste Agency), created by Executive Decree No. 02-175 of May 20, 2002. Placed under the supervision of the Ministry of the Environment and Renewable Energies, it is responsible, within the framework of a mission, to provide a public service to inform and popularize the techniques of sorting, collection, transport, treatment, recovery, and disposal of waste. It capitalizes on and constitutes a documentary base on waste management and ensures its dissemination to local authorities and the business sector. It also implements the programs and strategies of the aforementioned Ministry in the field of closing and rehabilitating illegal waste dumps.